Improving Students Skills In Organization Goals Formulation And Human Relations Development Through Training And Coaching - Hendrawan, Dimas (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2024)
Organization goals are future conditions that will be achieved by the organization. Preparing organizational goals is the responsibility of individuals and groups within the organization so it requires appropriate techniques that are carried out formally and effectively. This community service activity was held in order to improve students' abilities and skills in formulating organizational goals appropriately. Apart from that, this activity also aims to provide an understanding of human relations in relation to conflict as an obstacle to achieving organizational goals. This community service activity was carried out in two stages, namely a survey and analysis related to the process of preparing organizational goals carried out by students and the second stage was training in preparing organizational goals and implementing human relations as a strategy that supports the achievement of organizational goals.Keywords: organization goals, human relations, conflicts in organization